Durability of Strain-Hardening Fibre-Reinforced Cement-Based Composites (SHCC) - Van Zijl, G.P.A.G; Wittmann, F.H (RILEM State-of-the-Art Reports,, 2011)
Strain-Hardening Fibre-Reinforced Cement-Based Composites (SHCC) were named after their ability to resist increased tensile force after crack formation, over a significant tensile deformation range. The increased resistance is achieved through effective crack bridging by fibres, across multiple cracks of widths in the micro-range. Whether these small crack widths are maintained under sustained, cyclic or other load paths, and whether the crack width limitation translates into durability through retardation of ingress of moisture, gas and other deleterious matter, are scrutinized in this book by evaluation of test results from several laboratories internationally. The durability of SHCC under mechanical, chemical, thermal and combined actions is considered, both for the composite and the fibre types typically used in SHCC. The compilation of this state-of-the-art report has been an activity of the RILEM TC 208-HFC, Subcommittee 2: Durability, during the committee life 2005-2009.